2020
DOI: 10.1002/art.41157
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ Memory Stem T Cells Recognizing Citrullinated Epitopes Are Expanded in Patients With Rheumatoid Arthritis and Sensitive to Tumor Necrosis Factor Blockade

Abstract: Objective Memory stem T (Tscm) cells are long‐lived, self‐renewing T cells that play a relevant role in immunologic memory. This study was undertaken to investigate whether Tscm cells accumulate in rheumatoid arthritis (RA). Methods The polarization and differentiation profiles of circulating T cells were assessed by flow cytometry. Antigen‐specific T cells were characterized by staining with major histocompatibility complex class II tetramers. The T cell receptor (TCR) repertoire was analyzed by high‐throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
(55 reference statements)
4
24
0
Order By: Relevance
“…Recently, a study revealed that CD4 + Tscm cells were expanded in CD4 + T lymphocytes of RA patients and citrullinated vimentin (Vim cit )-specific CD4 + Tscm cells were increased in active RA patients (32). These findings confirmed our current study results in terms of expansion of CD4 + Tscm cells and CD8 + Tscm cells in RA patients even though statistical significance (in case of CD8 + Tscm cells) was not reached in the previous report.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, a study revealed that CD4 + Tscm cells were expanded in CD4 + T lymphocytes of RA patients and citrullinated vimentin (Vim cit )-specific CD4 + Tscm cells were increased in active RA patients (32). These findings confirmed our current study results in terms of expansion of CD4 + Tscm cells and CD8 + Tscm cells in RA patients even though statistical significance (in case of CD8 + Tscm cells) was not reached in the previous report.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, rheumatoid arthritis (RA) patients exhibit memory CD4 + T cells specific for various citrullinated antigens, including citrullinated aggrecan and citrullinated vimentin, which correspond to autoantibodies directed against citrullinated antigens and proteins in these patients [165][166][167]. Furthermore, CD4 + memory cells with a Th17 phenotype and specific for a citrullinated vimentin epitope expanded more significantly in RA patients with active disease and significantly decreased upon anti-TNF treatment [168]. Additionally, memory CD4 + T cells recognizing glycosylated type II collagen peptides have been identified in RA patients [169].…”
Section: Role Of Autoantigen For Memory T Cellsmentioning
confidence: 99%
“…An advantage of the blood‐tumor overlap analysis is that this analysis can enrich tumor‐associated T‐cell clones in the blood. The blood TCR repertoire contains clones that are not associated with cancer, such as virus‐specific clones 27 and autoreactive clones 28,29 . Thus, it is unclear to what extent the blood TCR repertoire changes represent antitumor T‐cell responses during PD‐1 blockade therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The blood TCR repertoire contains clones that are not associated with cancer, such as virus‐specific clones 27 and autoreactive clones. 28 , 29 Thus, it is unclear to what extent the blood TCR repertoire changes represent antitumor T‐cell responses during PD‐1 blockade therapy. Indeed, the clonality of the blood T‐cell repertoire containing both overlapping and nonoverlapping clones exhibited only weak associations with responses to PD‐1 blockade in this study.…”
Section: Discussionmentioning
confidence: 99%